The lncRNA ADAMTS9-AS2 Regulates RPL22 to Modulate TNBC Progression via Controlling the TGF-β Signaling Pathway - Ni, Kan; Huang, Zhiqi; Zhu, Yichun; Xue, Dandan; Jin, Qin; Zhang, Chunhui; Gu, Changjiang (Frontiers in Oncology, 2021)
Background Long non-coding RNAs (lncRNAs) are key regulators of triple-negative breast cancer (TNBC) progression, but further work is needed to fully understand the functional relevance of these non-coding RNAs in this cancer type. Herein, we explored the functional role of the lncRNA ADAMTS9-AS2 in TNBC. Methods Next-generation sequencing was conducted to compare the expression of different lncRNAs in TNBC tumor and paracancerous tissues, after which ADAMTS9-AS2differential expression in these tumor tissues was evaluated via qPCR. The functional role of this lncRNA was assessed by overexpressing it in vitro and in vivo. FISH and PCR were used to assess the localization of ADAMTS9-AS2within cells. Downstream targets of ADAMTS9-AS2 signaling were identified via RNA pulldown assays and transcriptomic sequencing. Results The expression ofADAMTS9-AS2 was decreased in TNBC tumor samples (P < 0.05), with such downregulation being correlated with TNM stage, age, and tumor size. Overexpressing ADAMTS9-AS2 promoted the apoptotic death and cell cycle arrest of tumor cells in vitro and inhibited tumor growth in vivo. From a mechanistic perspective, ADAMTS9-AS2 was found to control the expression of RPL22 and to thereby modulate TGF-β signaling to control TNBC progression. Conclusion ADAMTS9-AS2 controls the expression of RPL22 and thereby regulates TNBC malignancy via the TGF-β signaling pathway.